Concepts in Dental Public Health / Jill Mason - Mason, Jill
Written specifically for dental hygienists, this comprehensive textbook covers concepts, issues, techniques, and methods related to dental public health. It focuses on the assessment of factors that affect oral health of populations and the development of policy in response to a population's needs. It also provides information regarding the active promotion of oral health maintenance.